Virtual screening–based discovery of AI-2 quorum sensing inhibitors that interact with an allosteric hydrophobic site of LsrK and their functional evaluation - Shi, Qianqian; Wen, Huiqi; Xu, Yijie; Zhao, Xu; Zhang, Jing; Li, Ye; Meng, Qingbin; Yu, Fang; Xiao, Junhai; Li, Xingzhou (Frontiers in Chemistry, 2023)
Abstract Introduction: Quorum sensing (QS) is a bacterial intracellular and intercellular communication system that regulates virulence factors synthesis, biofilm formation, and antibiotic sensitivity. Quorum-sensing inhibitors (QSIs) are a novel class of antibiotics that can effectively combat antibiotic resistance. ATP-binding site of Lsr kinase (LsrK) is an important target for the development of autoinducer-2(AI-2) QSIs. Methods: In this study, we developed a workflow for molecular dynamics (MD) simulation, virtual screening and bioassay evaluation of AI-2 QSIs against the ATP-binding site of LsrK. Results: The MD simulation results of the LsrK/ATP complex revealed hydrogen bond and salt bridge formation among four key residues: Lys 431, Tyr 341, Arg 319, and Arg 322, which are critical for ATP binding to LsrK. At the ATP-binding site, an allosteric hydrophobic pocket was discovered, which can be occupied by small-molecule compounds. Therefore, we introduced the constraint of forming at least one hydrogen bond with these four key residues for Glide-based virtual screening. For visual inspection, compounds with hydrophobic groups that were likely to interact with the allosteric hydrophobic pocket were favored. Seventy-four compounds were selected for the wet laboratory assays based on ligand efficiency, structural diversity, and ADME properties. LsrK inhibition assays revealed 12 compounds with greater than 60% inhibition of LsrK at 200 μM, four of which had IC50 values below 50 μM and were confirmed as ATP competitive inhibitors. Six of these inhibitors exhibited high AI-2 QS inhibition, of which, Y205-6768 had the highest activity with IC50 = 11.28 ± 0.70 μM. Among them, compounds Y205-6768, D135-0149, and 3284-1358 exhibited high AI-2 QS inhibition, without suppressing bacterial growth. The SPR assay verified that compounds Y205-6768 and N025-0038 specifically bound to LsrK, with KD values of 8.49 × 10-6 M and 3.03 × 10-5 M, respectively. Molecular dynamics simulations were used to determine the most likely binding modes for Y205-6768, D135-0149, 3284-1358, and N025-0038, to LsrK. Binding mode analysis further confirmed the importance of hydrogen bonds and salt bridges formation with key basic amino acid residues and filling the allosteric hydrophobic pocket next to the purine-binding site for LsrK inhibitors.